Strategi Pembinaan Pelaku Usaha Kecil Pedesaan - Mado, Fitriana (Wacana Equiliberium (Jurnal Pemikiran Penelitian Ekonomi), 2018)
Small businesses as small-scale people's economic activities have a central role in the Indonesian economy. This small business is able to absorb labor, increase the number of business units, and support household income. Thus, to achieve this need to be fostered through training activities. This study aims to design the right strategy for fostering small businesses in Bahagia Villages in Palolo sub-district, Central Sulawesi province by analyzing the profile of the main businessmen based on entrepreneurial spirit (Entrepreneurship) and competence (competency). The type of research used is qualitative and qualitative research using an exploratory survey approach in cross sectional and action research.